Earnings Management and the Value Relevance of Sustainability Management: Evidence from Southeast Asian Countries - Frista, Frista; Gani, Lindawati; Abbas, Yulianti; Leo, Lianny (International Journal of Economics and Financial Issues, 2026)
This study investigates whether sustainability management leads to firm value and how the relationship is moderated by earnings management. Based on stakeholder theory and agency theory, we argue that although sustainability management can generate long-term value for firms. However, its credibility and value relevance may be questioned through earnings opportunistic activities. This study employs panel data of publicly listed firms across Southeast Asian (ASEAN) countries over the period 2015–2022 using panel regression analysis with robust estimates. Our findings show that sustainability management positively influences firm value. However, this positive effect is significantly reduced when firms engage in higher levels of accrual earnings management. These results add to the existing literature on ESG credibility, greenwashing issues, and sustainable value creation. This study offers several contributions. First, it expands the ESG and SDGs approach in the sustainability literature by including earnings management as a moderating factor. This offers a clearer understanding of how sustainability practices are viewed by capital markets. Second, it provides valuable evidence for investors, regulators, and policymakers interested in sustainable finance and corporate transparency.